Retention of Episomes During Protoplasting and During Propagation in the L State - Kawakami, Masaya (1966)
Kawakami, Masaya (Georgetown University, Washington, D.C.), and Otto E. Landman. Retention of episomes during protoplasting and during propagation in the L state. J. Bacteriol. 92:398–404. 1966.—In earlier work, it was observed that the mesosomes of Bacillus magaterium and B. subtilis are expelled from the cell interior during protoplasting and that mesosome fragments are released into the supernatant fluid as the cell wall disintegrates. Since the resultant protoplasts remain intact and capable of reproduction, the expelled contents of the mesosome “bag” are presumably external to the protoplast membrane and nonessential to survival. Accordingly, if episomes (plasmids) were localized in the extramembrane mesosome “bag,” it would be predicted that protoplasting would cure cells of their episomes. This prediction was tested in three different systems: B. subtilis W23 carrying phage SP-10, B. megaterium 216 carrying megacinogenic factors A and C, and B. megaterium C4M(−) carrying megacinogenic factor C. No curing due to protoplasting was observed. Even during propagation in the L form, when septation is not functioning and the distribution of deoxyribonucleic acid to daughter cells is severely disrupted, curing was not observed in any of the above systems nor in Salmonella L forms carrying F(0)lac. It is concluded that episomes are located at a position on the interior side of the cell membrane and that their distribution to daughter cells is coordinated with that of the chromosome.